Designing an Interactive Map as a Medium for Information on Facilities and MSMEs in Sukajaya Village, Way Khilau, Pesawaran - Andhiva Rifky Nugraha; Rohiman Rohiman (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The development of digital technology has changed the way people access and manage information, but the digital divide remains a challenge in some areas, including Pesawaran Regency, Lampung Province. This study aims to design and implement a digital-based interactive map as a medium of information on public facilities and micro, small, and medium enterprises (MSMEs) in Sukajaya Village, Way Khilau District. This study uses a qualitative descriptive method with a case study approach, through field observations, documentation, and literature reviews to understand the spatial, social, and economic conditions of the community. The design process integrates 5W+1H analysis and mind mapping to formulate a user-based information structure, while Adobe Illustrator and Figma are used in the visual digitisation and interactive interface development stages. The results of the study show that interactive maps can improve access to information, strengthen the visibility of local MSMEs, and encourage community participation in sustainable village development. This study concludes that interactive digital media is an effective solution to bridge the digital divide and support inclusive economic growth at the village level.